2021
DOI: 10.1016/j.bbi.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of astroglial toll-like receptors (TLRs) in central nervous system infections, injury and neurodegenerative diseases

Abstract: Highlights Astroglial TLRs mediate host-defense and pathogen dissemination in CNS infections. Astroglial TLRs help clearance of protein aggregates in neurodegenerative diseases. Astroglial TLR signaling contributes to inflammation in CNS injury and disease. Signaling through TLRs promotes beneficial and detrimental functions of astrocytes. TLRs in astrocytes could be therapeutic targets in CNS disease and injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(150 citation statements)
references
References 277 publications
(318 reference statements)
2
146
0
2
Order By: Relevance
“…Besides, exposure to the viruses or their components promotes the expression and activation of Toll-like receptors (TLR) in astrocytes. This signaling promotes the production and release of proinflammatory mediators and induces inflammatory responses in the CNS (Figure 2B step 3), eliminating the pathogen as demonstrated for Flavivirus infections (82,120). Therefore, this pathological signaling causes neuronal degeneration and dysfunction of the nerve cells short or long term.…”
Section: Can the Systemic Inflammation By Covid-19 Trigger Neurovascular Disturbance?mentioning
confidence: 93%
“…Besides, exposure to the viruses or their components promotes the expression and activation of Toll-like receptors (TLR) in astrocytes. This signaling promotes the production and release of proinflammatory mediators and induces inflammatory responses in the CNS (Figure 2B step 3), eliminating the pathogen as demonstrated for Flavivirus infections (82,120). Therefore, this pathological signaling causes neuronal degeneration and dysfunction of the nerve cells short or long term.…”
Section: Can the Systemic Inflammation By Covid-19 Trigger Neurovascular Disturbance?mentioning
confidence: 93%
“…S. aureus triggers TLR2 signaling in astrocytes and the secretion of NO, IL-1β, and TNF-α via NF-kB- and MAPK-dependent pathways ( 156 ). Other studies have shown that TLR activation induces astrocyte chemokine production (CCL2, CCL3, CCL5) and augments adhesion molecule expression ( 157 , 158 ). In astrocytes, the intracellular pattern recognition receptor NOD2 was shown to activate NF-kB leading to IL-6, TNF-α, and co-stimulatory molecule expression, which amplified the anti-bacterial immune response ( 159 ).…”
Section: Other Cell Types In the Brain During S Aureus mentioning
confidence: 98%
“…Furthermore, astrocytes and microglia have been shown to play an important role in neuroinflammation processes, responding to local inflammation of the CNS and imbalanced peripheral inflammation (Murta et al, 2020). SARS-CoV-2 also is neuro-invasive and can spread to the brain, causing a chronic immune imbalance, which underlies possible long-term effects on synapses and neuropsychiatric disorders (Wu and Tang, 2020;Li et al, 2020). Furthermore, accumulating evidence has shown that neuroglia is the target of several neurotropic viruses that severely affect its function.…”
Section: Possible Mechanism Of Neurological Damagementioning
confidence: 99%